Socio-Cultural Dynamics of Education in the Context of the Post-Non-Classical Science - V. A. Ignatova (Образование и наука)
The paper deals with the interrelations between society, education and culture. Using the comparative analysis of classical approaches to defining the above spheres, the author comes to conclusion that the nature of socio-cultural processes can be explored and described most consistently by applying comprehensive models of the post-non-classical science and considering civilization, education and culture in the context of the unified dynamic flow of socio-cultural genesis. The research investigates the dialectics of socio-cultural processes in the light of systematic synergetic approach, the advancing role of education in socio-cultural dynamics being revealed and substantiated. The author emphasizes its inevitably rising priority due to sustained development of civilization bringing about the new environmentally-oriented meta-culture.The obtained results can be used in pedagogic research methodology, designing and modeling the educational process, its content, technology and organization.